2017
DOI: 10.2174/1874149501711010464
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Design Criteria for Concentric V-Braced Steel Structures According to Italian and European Codes

Abstract: Abstract:The critical review of design methodologies provided by the NTC2008, in agreement with the European seismic code (Eurocode 8) for steel Concentrically Braced Frames with chevron (or inverted V) diagonals (CBF-V), carried out by deepening the seismic behaviour of such typical steel seismic resistant structures, aims to provide more efficient design criteria able to ensure adequate safety levels under seism.As reference case studies, common structural configurations of CBF-V are designed according to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A critical review of design methodologies has been made with the scope of providing simplified and more efficient design criteria and procedures, according to the modern design approach, able to ensure adequate safety levels under seismic actions [25]. Some theoretical-numerical studies have been developed on inverted CBF-V by considering common structural configurations of with 3, 6 and 10 storeys, designed according to the current standard provisions by using both linear static and dynamic analyses [26]. The consequences of the use either circular hollow sections (CHS) or HE profiles for braces has been analyzed.…”
Section: Concentric Bracingsmentioning
confidence: 99%
“…A critical review of design methodologies has been made with the scope of providing simplified and more efficient design criteria and procedures, according to the modern design approach, able to ensure adequate safety levels under seismic actions [25]. Some theoretical-numerical studies have been developed on inverted CBF-V by considering common structural configurations of with 3, 6 and 10 storeys, designed according to the current standard provisions by using both linear static and dynamic analyses [26]. The consequences of the use either circular hollow sections (CHS) or HE profiles for braces has been analyzed.…”
Section: Concentric Bracingsmentioning
confidence: 99%
“…In line with [18], this work critically discusses about (i) the ductility classes and the correlated force-reduction factors; (ii) the structural analysis methods permitted by different codes; (iii) the detailing rules for both dissipative (bracing members) and nondissipative elements. The second paper describes the results of a numerical study carried out by Faggiano et al [19] aimed at investigating the seismic performance of inverted V concentrically braced frames designed according to [15, . The results show that the examined structures experience poor seismic performance without tensile yielding of bracing members.…”
mentioning
confidence: 99%
“…Specifically for Chevron Braced Frames (CBF-V), the ratio between the beam flexural stiffness and the braces vertical stiffness is recognized as affecting the overall performance and the damage of braces under compression [6]. In this context an overview on the codification aspects according to the Italian technical Code (NTC08) and the Eurocode 8 is presented [7,8], evidencing some critical issues both in the design process and in the seismic capacity of structures evaluated through non-linear static analyses. In particular, it is observed that current design criteria lead to structures that behave better than expected, in terms of ductility and dissipative capability, being the behaviour factors calculated larger than the design value, although the ideal collapse condition is not attained, a local beam mechanism occurring at the top story, in absence of brace plastic behaviour in tension.…”
mentioning
confidence: 99%
“…2 THE CASE STUDIESThe study structures belong to in-plan and in-elevation regular buildings with 3, 6 and 10 storeys [7]. The geometric features of the structural model are shown in Figure 1.…”
mentioning
confidence: 99%
See 1 more Smart Citation